Insights for Global Development Solutions - World Bank Group (World Bank, Washington, DC, 2018)
The Development Digest is a half-yearly publication that features key works from teams based at the World Bank Group Global Knowledge and Research Hub in Malaysia. This third issue of the Development Digest focuses on green Islamic financing, where Malaysia leads the way with the issuance of the world's first green corporate sukuk. This digest also looks into topics like ASEAN at 50, open data, the role of GDP in development, migration, and microfinance. Other articles include one on industrial policies versus public goods to spur growth, and another on economic forecasting.